Analisis Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah - Annisa, Nurul; Fitra, Halkadri (Jurnal Nuansa Karya Akuntansi, 2025)
This research examines the influence of Human Resource Competence, Utilization of Information Technology, Organizational Commitment, Government Accounting Standards, and Good Government on the Quality of Local Government Financial Reports. Using a quantitative approach, data were collected through questionnaires from 60 Regional Apparatus Organizations (OPD) employees in Padang City, selected through purposive sampling. Data analysis was conducted using Multiple Linear Regression Analysis to measure the simultaneous effects of these factors on the quality of financial reports. The results indicate that human resource competence and utilization of information technology have a significant positive effect on the quality of financial reports. Organizational commitment has a minor effect. Government accounting standards and good government also have a significant positive effect, enhancing the transparency and accountability of financial reports. Overall, the competence of human resources, information technology, accounting standards, and good governance are important for improving the quality of financial reports, while organizational commitment has little impact.